Development and validation of a simple HPLC assay for the quantitation of SM-1, a novel derivative of the PAC-1 anticancer agent, and an initial pharmacokinetics study in rats. Issue 22 (21st October 2015) - Ji, Shan; Li, Meizhen; Zhou Wen,; Li, Jie; Li, Sanwang; Xie, Feifan; Cheng, Zeneng
Abstract : A sensitive and reliable HPLC-UV method for the determination of SM-1, a novel derivative of the PAC-1 anticancer agent, in rat plasma was established and applied to a preclinical pharmacokinetics study. Abstract : A simple and specific HPLC-UV method was developed and validated for the determination of SM-1 in rat plasma. The bioanalytical procedure involved extraction of SM-1 and gefitinib (internal standard, IS) from a 100 μL plasma aliquot with simple protein precipitation with methanol. Chromatographic separation was achieved using an Agilent TC-C18 column (4.6 mm × 150 mm, 5 μm) with an isocratic mobile phase consisting of 10 mM potassium hydrogen phosphate solution (pH 7.0, adjusted by using 10% phosphoric acid)–acetonitrile (37 : 63, v/v) at a flow-rate of 1.0 mL min −1 . The UV detection wavelength was 282 nm. SM-1 and IS eluted at 3.6 and 7.0 min, respectively, with a total run time of 8 min. Method validation was performed according to US Food and Drug Administration bioanalytical guidelines and the results met the acceptance criteria. The calibration curve of SM-1 in rat plasma was linear over the concentration range of 0.1–20 μg mL −1 . Intra- and inter-run precisions of SM-1 were less than 6.1% and the biases were within ±10.0%. The method was successfully applied to the pharmacokinetics study after intravenous and oral administration of SM-1 in rats.